The low-temperature germinating spores of the thermophilic Desulfofundulus contribute to an extremely high sulfate reduction in burning coal seams - Karnachuk, Olga V.; Rusanov, Igor I.; Panova, Inna A.; Kadnikov, Vitaly V.; Avakyan, Marat R.; Ikkert, Olga P.; Lukina, Anastasia P.; Beletsky, Alexey V.; Mardanov, Andrey V.; Knyazev, Yuri V.; Volochaev, Mikhail N.; Pimenov, Nikolai V.; et al. (Frontiers in Microbiology, 2023)
Burning coal seams, characterized by massive carbon monoxide (CO) emissions, the presence of secondary sulfates, and high temperatures, represent suitable environments for thermophilic sulfate reduction. The diversity and activity of dissimilatory sulfate reducers in these environments remain unexplored. In this study, using metagenomic approaches, in situ activity measurements with a radioactive tracer, and cultivation we have shown that members of the genus Desulfofundulus are responsible for the extremely high sulfate reduction rate (SRR) in burning lignite seams in the Altai Mountains. The maximum SRR reached 564 ± 21.9 nmol S cm -3 day -1 at 60°C and was of the same order of magnitude for both thermophilic (60°C) and mesophilic (23 °C) incubations. The 16S rRNA profiles and the search for dsr gene sequences in the metagenome revealed members of the genus Desulfofundulus as the main sulfate reducers. The thermophilic Desulfofundulus sp. strain Al36 isolated in pure culture, did not grow at temperatures below 50°C, but produced spores that germinated into metabolically active cells at 20 and 15 °C. Vegetative cells germinating from spores produced up to 0.738 ± 0.026 mM H2S at 20 °C and up to 0.629 ± 0.007 mM H2S at 15 °C when CO was used as the sole electron donor. The Al36 strain maintains significant production of H2S from sulfate over a wide temperature range from 15 to 65 °C, which is important in variable temperature biotopes such as lignite burning seams. Burning coal seams producing CO are ubiquitous throughout the world, and biogenic H2S may represent an overlooked significant flux to the atmosphere. The thermophilic spore outgrowth and their metabolic activity at temperatures below the growth minimum may be important for other spore-forming bacteria of environmental, industrial and clinical importance.